International accounting - Lawrence, Steve. (International Thomson Business Press, 1996)
This book contains the details of accounting systems in many different countries; the basic factors that can shape those systems, details of the technical accounting issues that confront the accountants of this world, and an assessment of the problems of analysing and interpreting foreign financial statements.